Jumlah Trombosit pada Mencit Diabetes setelah Pemberian Ekstrak Rumput Laut Merah (Rhodophyceae) - Dahna Maudita Kartikasari; Didin Erma Indahyani; Depi Praharani (Pustaka Kesehatan, 2019)
Oxidative stress in diabetes mellitus triggers activation and increases in platelet counts that play a role in the formation of platelet plugs in the blood clotting process. If excessive blood clots occur, there is a risk of cardiovascular disease. Red seaweed extract contains carotenoids, phenols and their derivatives, fikobilin pigments, polysaccharide sulfates, and vitamins. The biggest phenol compound is flavonoids which are compounds that can produce platelet antia-gregation effects. The purpose of this study was to examine the effect of giving red seaweed extract to platelet counts in diabetic mice. The study group consisted of the treatment group of red seaweed extract, normal control, positive control and negative controls. The dosage of seaweed extract as much as 10 mg / 20 grBB is given in condition. The calculation of platelet count is carried out directly with the Brecher Cronkite method using a calculated room Improved Neubauer. The One Way ANOVA test results showed a significance value (p <0.05), that is, the group of diabetic mice given red seaweed extract had a lower platelet count of 280000 μl compared to diabetic mice given metformin as much as 379000 μl. The decrease is due to flavonoids, saponins, alkaloids, β carotene, vitamins and minerals able to stabilize the production of megakaryocytes and platelets, prevent the destruction of pancreatic β cells and prevent free radicals. It was concluded that red seaweed extract can reduce platelet counts of diabetic mice near normal values.